The effects of self-congruity and functional congruity on tourists’ loyalty in theme parks - Gang, Xu; Rehman, Asad Ur; Nawal, Ayesha; Ullah, Ihtisham; Hussain, Kashif (Edelweiss Applied Science and Technology, 2025)
In this study,the structural equation model of the impact of self-congruity and functional congruity on tourism behavior was applied to the research of tourists’ loyalty in theme parks for the first time.The purpose of the study is to construct and test a conceptual framework integrating self-congruity,functional congruity,tourists' loyalty in theme parks.A sample of 370 tourists was collected from the four major theme parks in Wuxi via questionnaires.SPSS 22 and AMOS 24 were employed to analyse the data.The findings indicate as follows: firstly, self-congruity positively influences functional congruity;secondly, functional congruity completely mediates the cause-effect relationship between self-congruity and tourists’ loyalty in theme parks;thirdly, functional congruity positively impacts tourists’ loyalty in theme parks;fourthly, self-congruity does not directly influence tourists’ loyalty in theme parks.According to the findings,suggestions were made for theme park marketers and managers.This study provides a new perspective of increasing tourists’loyalty in theme parks by introducing self-congruity and functional congruity variables into the research field of tourists' loyalty in theme parks.